Goods trade liberalization under the ASEAN Economic Community effects on the Philippine economy - Clarete, Ramon L.; Tuano, Philip Arnold P. (The Philippine Review of Economics, 2015)
The economy-wide effects of the Asean Free Trade Area (AFTA) on the Philippine economy are computed using the Global Trade Analysis Project (GTAP) model of the world economy. Of the 40 industries representing the Philippine economy that were simulated to assess the impacts of AFTA on sectoral output, 24 industries declined. However, the order of magnitudes of the percentage declines is low, except for rice, whose output decreased by about 4.5 percent.